2017
DOI: 10.1080/0284186x.2017.1398414
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography (CBCT) for adaptive image guided head and neck radiation therapy

Abstract: The tested dose surveillance algorithm resulted in a minimal dose reduction ( ≤1 Gy) to parotid glands for three of 40 patients. The proposed algorithm and workflow is thus not sustainable. Mid-course dose verification did not provide added benefit and can be safely omitted in the presence of closely monitored daily IGRT. Daily image guidance and match protocol is a safe and efficient method for identifying patients requiring adaptive replanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…It is therefore crucial to target patients with OAR overdose and/or target volume underdose. Systematic weekly dose surveillance based on CBCT resulted in an increased workload (100 min per patients) for a limited parotid gland dose decrease (<1 Gy) among a limited number of patients [58]. Ideally, replanning decisions should be based on early and simple anatomical predictors, with a clear objective of parotid gland overdose and/or tumor underdose correction.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore crucial to target patients with OAR overdose and/or target volume underdose. Systematic weekly dose surveillance based on CBCT resulted in an increased workload (100 min per patients) for a limited parotid gland dose decrease (<1 Gy) among a limited number of patients [58]. Ideally, replanning decisions should be based on early and simple anatomical predictors, with a clear objective of parotid gland overdose and/or tumor underdose correction.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed re-planning in 5 out of 110 patients (4.5%). In a study of Hvid et al RTTs performed daily treatment setup guided CBCT scans and recorded irregularities such as the need for manual adjustment of the treatment position after bony anatomy match, couch shifts > 3 degrees or > 1 cm change in body contour [21]. In their CBCT cohort, a total of 21 replans were performed in 17 out of 60 patients (28%).…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al preformed scheduled rescans mid-treatment and used CBCT scans to examine if the variations (systematic or random) were consistent by checking the position of the spinal cord, skull and upper neck [24]. Hvid et al on the other hand concluded that the presence of daily CBCT imaging, mid-course CT does not provide any added benefit, provided that skilled RTTs follow a match protocol to identify patients in need of adaptive re-planning [21]. Our findings are in line with these series.…”
Section: Discussionmentioning
confidence: 99%
“…A verification process such as described here would increase availability on CT for all treatment sites within this busy department, whilst potentially reducing patient anxiety as many expect 'results' from the repeat planning CT. The safe omission of repeat CT during H&N RT has been previously justified [4,31]. Many institutions already acknowledge the benefit of rigid registrations using CBCT for on-treatment image guidance; and identifying anatomical changes.…”
Section: Verification At Mid-treatment Sct Vs Pct2mentioning
confidence: 99%